Ischemic stroke associated with novel coronavirus 2019: a report of three cases. (2nd December 2021) - Sharifi-Razavi, Athena; Karimi, Narges; Zarvani, Ashraf; Cheraghmakani, Hamed; Baghbanian, Seyed Mohammad
Abstract: Introduction: There is limited evidence about the neurological manifestations of COVID-19 in infected patients. In this report, we describe three patients with ischemic stroke associated with COVID-19 infection. Methods: We report 3 cases of adult patients with ischemic stroke and novel coronavirus 2019 infection. Case 1 is an 88-year-old female with acute left hemiplegia and right peripheral facial paresis that she had a fever along with stroke symptoms. Case 2 is an 85-year-old female with left hemiplegia and drowsiness who had a weakness, asthenia, and dry cough 3 days before appearing stroke signs. Case 3 is a 55-year-old male with acute Brocaʼs aphasia and right hemiplegia who experience fever and respiratory problems 3 days after admission. Results: The clinical symptoms of infected patients with COVID-19 have been associated with severe symptoms of ischemic stroke. Two patients were admitted to the ICU. RT-PCR of the oropharyngeal sample was positive in three cases. All patients had the involvement of large cerebral arteries. Conclusion: The mechanism by which COVID-19 causes ischemic stroke is unknown but it is likely by production inflammatory cytokines or direct infection of cerebral arteries. Therefore, regarding the current situation of the COVID-19 pandemic, it is indispensable that the possible diagnosis of COVID-19 vasculopathy is considered in all ischemic strokes of unclear etiology.